Thermal, Biodegradability And Water Barrier Properties Of Bio-Nanocomposites Based On Plasticised Sugar Palm Starch And Nanofibrillated Celluloses From Sugar Palm Fibres - Ilyas, R. A.; Sapuan, S. M.; Zainudin, E. S.; Ibrahim, Rushdan; Abral, Hairul; Ishak, M. R.; A. Atiqah, A. Atiqah; M. S. N. Atikah, M. S. N. Atikah; Edi Syafri, Edi Syafri; Mochamad Asrofi, Mochamad Asrofi; Jumaidin, Ridhwan (American Scientific Publishers, 2020)
Sugar palm (Arenga pinnata) starch and fibre are considered as a waste product of the agroindustry. The purpose of the current study is to determine the thermal, water barrier, and soil degradation properties of biodegradable plasticised sugar palm starch (PSPS) that contains sugar palm nanofibrillated celluloses (SP-NFCs) derived from sugar palm fibre. The bio-nanocomposites were fabricated by using the solution-casting method with the nanocellulose contents in the range of 0.1 wt.%–1.0 wt.%. The thermal stability, water resistance and degradation behaviour improved with increase in SP-NFCs content, due to high compatibility and strong inter-molecular hydrogen bonds formed between PSPS and SP-NFCs. PSPS/SP-NFCs bio-nanocomposites with 1.0 wt.% SP-NFCs content displayed the highest mechanical and thermal stability. Residue that was left during the TGA analysis increased as the SP-NFCs content was increased. Soil burial tests showed biodegradability resistance of the bio-nanocomposites. The following conclusions can be drawn from the present reinforcement study of SP-NFCs enhanced biodegradability, water barrier as well as thermal properties of starch polymer which extended the prospective application of environmentally-friendly polymer material. Potential applications for this eco-material are short product life cycles (plastic packaging and food container).